Behavioural And Hippocampal Neuroplasticity Effects Of A Bioactive Fraction From Clitoria Ternatea Linn. Root Extract In A Rat Model Of Chronic Cerebral Hypoperfusion - Ahad, Mohamad Anuar (2022)
Pharmacological therapy is highly recommended for reducing the severity of the behavioural and psychiatric syndromes of dementia, as well as for effectively reversing cognitive decline in symptomatic dementia patients. Scientific evidence on cognition-oriented approaches for treating cognitive impairment using natural-based products is well discovered. Therefore, the thesis investigates the effects of bioactive fraction from Clitoria ternatea (CT) root extract in the behavioural and hippocampal neuroplasticity in chronic cerebral hypoperfusion (CCH) rats model. The bioassay-guided fractionation approach was carried out to produce the CT root bioactive fraction. To begin with, CT root powder was extracted using sequential extraction of solvent varying polarity. Then, the extracts were screened for their bioactivity using in vitro and in vivo studies. The CT root chloroform extract was further subjected to fractionation and isolation compound(s) using column chromatography to produce the bioactive fraction and active compound(s). The amount of clitorienolactone A (CLA) in the CT root bioactive fraction (255 mg/g) and active extract (150 mg/g) was quantified using high-performance liquid chromatography and diode array detection analysis for quality control purposes.